Influence of hydrostatic pressure on texture evolution in HPT deformed NiAl. Issue 1 (April 2015) - Tränkner, C; Chulist, R; Skrotzki, W; Lippmann, T; Horky, J; Zehetbauer, M
Abstract: NiAl is an intermetallic compound with a brittle-to-ductile transition temperature of about 300°C at ambient pressure. At standard conditions, it is very difficult to deform, but fracture stress and fracture strain are increased under hydrostatic pressure (HP). On account of this, deformation at low temperatures is only possible at high HP, as for instance used in high pressure torsion (HPT). In order to study the influence of HP on texture evolution, small discs of polycrystalline NiAl were deformed by HPT at different temperatures ranging from room temperature to 500°C and different HPs. The influence of HP is presented for deformation at room temperature and 500°C. It is found that HP affects the formability of the samples as well as texture and microstructure.